Do you have answer options for this question?
Answer:
Answer is A
Step-by-step explanation:
They start at -10 and if you add 10 you get 0. You increase
Answer:
-4
Step-by-step explanation:
If a = -4 then you can eliminate hte -4x and 4x by adding them, you get 0x, so you eliminate the x variable
Answer:
Step-by-step explanation:
y = -4x^2 + 4x + 6
Factor out the leading coefficient:
y = -4(x^2 - x) + 6
Complete the square:
y = -4(x^2 - x + (½)^2) + 4(½)^2 + 6
= -4(x-½)^2 + 7
Answer:
55
Step-by-step explanation:
hope it helps you.....